Evaluate Pediatric Caregivers’ Musculoskeletal Health Literacy in General Pediatric Orthopedic Clinic in Saudi Arabia, 2024 - Nouf Ajlan Alqurashi; Muhannad Khaled Badghaish; Jawahr Abdulaziz Hamad Bin Akail; Abdulrahman Mohammed Al Shehri; Amjad Ahmed Alshareef; Mohammed saad almasoudi; Malak Talal Jameel Alhazmi Alharbi; Riyadh Ghazali Banjar; Hesham Salah Hasan Ebid; Hassan Abdullah Mohammed Balkhi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Musculoskeletal health is a global concern for school-age children. Children often face ergonomic risk factors in their daily activities, so it is important to raise parental awareness to prevent musculoskeletal disorders in their children.Health literacy (HL) related to musculoskeletal disorders (MSDs) in children is a field with limited previous evidence. The study aimed: To evaluate pediatric caregivers’ musculoskeletal health literacy and risk factors for lack of health literacy in general pediatric orthopedic clinic. Methods and Materials:A cross-sectional study was conducted among a convenience sample of 200 caregivers of children presenting with musculoskeletal complaints at the general pediatric orthopedic clinic of a hospital in Makkah, Saudi Arabia. Caregivers who were taking their children for either first-time or follow-up visits were included in the study. Participants were excluded if they did not meet the above-mentioned criteria, had any cognitive impairment, or were unable to sign their own consent. Caregivers completed a demographic survey, the Literacy in Musculoskeletal Problems questionnaire, and the Newest Vital Sign to measure musculoskeletal and general health literacy, respectively. Results: 46.7% of participants had low levels of musculoskeletal health. Additionally, 18.0% of individuals had inadequate general health literacy. The likelihood of worked in the healthcare industry (p = 0.0055), and those who had completed at least some college (p = <0.0012), according to multivariate logistic regression. Adequate general health literacy was only associated with at least some college experience (p = 0.003) according to multivariate logistic regression. Conclusion: Nearly half of all caregivers who bring their children to a pediatric orthopedic clinic are not educated in musculoskeletal health and may not have the knowledge needed to make wise decisions regarding their child’s care. Compared to limited general health literacy, limited musculoskeletal health literacy is more common.